2020
DOI: 10.1002/nbm.4416
|View full text |Cite
|
Sign up to set email alerts
|

Rapid MR relaxometry using deep learning: An overview of current techniques and emerging trends

Abstract: Quantitative mapping of MR tissue parameters such as the spin‐lattice relaxation time (T1), the spin‐spin relaxation time (T2), and the spin‐lattice relaxation in the rotating frame (T1ρ), referred to as MR relaxometry in general, has demonstrated improved assessment in a wide range of clinical applications. Compared with conventional contrast‐weighted (eg T1‐, T2‐, or T1ρ‐weighted) MRI, MR relaxometry provides increased sensitivity to pathologies and delivers important information that can be more specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 203 publications
(403 reference statements)
0
42
0
1
Order By: Relevance
“…MRF is a favorable approach to obtaining quantitative MR relaxation measurements. In addition, quantitative MR relaxometry can synthesize conventional contrast weightings [ 2 , 3 ], which can be useful for adherence to current clinical diagnostic standards. Furthermore, quantitative MRI relaxometry–based tissue segmentation was reported to have favorable repeatability [ 39 ] and can be beneficial in clinical settings for tracking the time course of a disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRF is a favorable approach to obtaining quantitative MR relaxation measurements. In addition, quantitative MR relaxometry can synthesize conventional contrast weightings [ 2 , 3 ], which can be useful for adherence to current clinical diagnostic standards. Furthermore, quantitative MRI relaxometry–based tissue segmentation was reported to have favorable repeatability [ 39 ] and can be beneficial in clinical settings for tracking the time course of a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative magnetic resonance (MR) relaxometry can quantify the relaxation time (e.g., T1, T2, T2* relaxation time) to clarify the physical and pathological properties of human tissues [ 1 ]. Quantitative MR relaxometry was reported to increase accuracy and precision compared with conventional weighted magnetic resonance imaging (MRI) in detecting lesions, and it can even synthesize traditional weighted images [ 2 , 3 ]. However, clinical applications of quantitative MR relaxometry are limited by the length of the imaging procedure required to estimate the tissue relaxation time; moreover, motion artifacts can interfere with the results, and the procedure does not meet the needs for clinical scheduling efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review provides an overview of five essential aspects of CMR which have been covered separately in-depth in other review papers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). We address: (1) data acquisition sequences and common artifacts, (2) clinical applications, (3) clinical examination protocols, (4) image acceleration, reconstruction, and motion handling, (5) artificial intelligenceassisted reconstruction and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The interface setup facilitates the comparison between Python-based and C++-based methods. Moreover, the Python language serves as a framework for deep learning libraries [14][15][16] and is commonly adopted for the development of deep learning algorithms, which may have potential for improving the performance in cardiac T1 mapping [17]. In an earlier study, we demonstrated fast T1 map calculation using the LM-based method implemented in C++, as a module for a comprehensive quantitative cardiac MRI analysis tool [18].…”
Section: Introductionmentioning
confidence: 99%